Analisis Skema Pengenaan Pajak Karbon Di Indonesia Berdasarkan United Nations Handbook Mengenai Penerapan Pajak Karbon Oleh Negara Berkembang - Bima Niko Pamungkas; Vissia Dewi Haptari (JURNAL PAJAK INDONESIA, 2022)
This study aims to find out whether there are similarities or differences in carbon tax policies in Indonesia compared to the UN Handbook regarding the implementation of carbon tax schemes by developing countries. The scope of the discussion itself is focused on 4 things: scope of the tax (object, subject and imposing method of the carbon tax), carbon tax rates, application design, and earmarking of carbon tax revenue. The data used were collected through library research methods and interviews with tax experts. The collected data then being analysed through thematic analysis by reducing the data through coding process. The results of this study indicate that there are similarities between carbon tax scheme in Indonesia and that contained in UNH. However, there are also differences that the authors found when these policies were juxtaposed.